Peran Pendamping (Paralegal) dalam Memberikan Perlindungan Hukum Bagi Perempuan Korban Kekerasan dalam Rumah Tangga - Cokorda lstri Dharmasatyari; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
This study aims to analyze the role of paralegals in The Indonesian Women's Alliance for Justice Legal Aid Institute and reveal the obstacles faced in solving problems in the sphere of women and also clearly study the role of mentoring for women who are victims of domestic violence. This study used empirical legal research with a statutory legal approach. Sources of data were primary and secondary legal materials obtained through interviews and assisted by literature studies from various literature. The results showed that the role of the paralegal was very important starting from the victim submitted a complaint and reported her complaint to LBH APIK, the paralegal gave considerations regarding the legal process that would be passed until the trial was carried out, and the legal process was completed. This assistance was intended to provide and increase feelings of security, comfort, and peace mentally and physically when the victim has this problem, and so that the victim did not get confused as well when the legal process took place. The obstacle to the lack of members made the existence of paralegals in each region ineffective.